Erratum: The link between relative pay and job satisfaction revisited (European Sociological Review DOI: 10.1093/esr/jcaa045) - Collischon, Matthias; Eberl, Andreas (European Sociological Review, 2021)
In the originally published version of this manuscript, the authors' names were not listed alphabetically to reflect equal authorship. This has now been corrected.
CRIS-Team Scopus Importer:2021-10-01